2012
DOI: 10.7439/ijbr.v3i3.366
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Death Review to Know the Determinants of Maternal Mortality in a District Hospital of Central India

Abstract: Background: Avoiding maternal deaths is possible even in resource-limited countries, but r correct information on which to base maternal health programmes is required. Knowing the level of maternal mortality is not enough to prevent further deaths; there is need to understand the underlying factors that led to the deaths. Maternal death review is one of the oldest and the most documented methods that can be effective in improving emergency obstetric care and maternal outcomes. Objectives: To study the maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 7 publications
3
20
0
Order By: Relevance
“…Previous study in India and abroad have reported that the extramural maternal death range from 31.2 to 76.4% whereas in our study it is 65.6%. [8][9][10][11] More higher mortality ratios had been found in the various studies [12][13][14][15][16][17] The majority of deaths in our study were in the age group 20 to 29 -64.3% which is in accordance with the age distribution of maternal death in India -MMR Bulletin of India 2011 to 2013 -where it is 68% in the age group 20 to 29 years. 18 The majority of maternal deaths were from the lower socio economic strata 75.7% and 69.1% of these mothers were multi gravida with spacing less than 3 years especially the unbooked mothers who were nomadic and illiterate who not only have resource constraint but are also not self-empowered to take their own decisions or to understand the seriousness of their situation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous study in India and abroad have reported that the extramural maternal death range from 31.2 to 76.4% whereas in our study it is 65.6%. [8][9][10][11] More higher mortality ratios had been found in the various studies [12][13][14][15][16][17] The majority of deaths in our study were in the age group 20 to 29 -64.3% which is in accordance with the age distribution of maternal death in India -MMR Bulletin of India 2011 to 2013 -where it is 68% in the age group 20 to 29 years. 18 The majority of maternal deaths were from the lower socio economic strata 75.7% and 69.1% of these mothers were multi gravida with spacing less than 3 years especially the unbooked mothers who were nomadic and illiterate who not only have resource constraint but are also not self-empowered to take their own decisions or to understand the seriousness of their situation.…”
Section: Discussionsupporting
confidence: 77%
“…These are the major risk factors of maternal mortality. 8 In our study the direct causes of maternal deaths are 40% hypertensive disorders complicating pregnancies, 30% haemorrhage, Anemia with failure -17.2%, Heart disease complicating pregnancies -6.8%, Sepsis -3.4%, other causes 3.4%. As per WHO 2010 13% of maternal deaths were due to hypertensive disorders complicating pregnancies, but in our study of the direct causes of maternal deaths, hypertensive disorders complicating pregnancies tops the list -40%.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Tayade et al reported an MMR of 242 at Wadgwa, Maharashtra where as Shivkumar et al reported MMR of 974 at VIMS Bellary, Karnataka. 10,11 Most mothers died in the age group 20-24 years (49.2%). Majority of them were unbooked (60%) and multigravidae (55.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that infants who lost their mother during childbirth are more likely to die before reaching their second birthday than infants whose mother survives. [3] In the present study, there were 62 maternal deaths out of 18,458 deliveries, presenting a maternal mortality ratio of 335 per 1,00,000 live births. This high maternal mortality can be attributed to the fact that the study was conducted in the tertiary care referral center.…”
Section: Discussionmentioning
confidence: 99%